Tolerance in the United States: Does economic freedom transform racial, religious, political and sexual attitudes? - Niclas Berggren; Therese Nilsson (Research Institute of Industrial Economics (IFN), 2015)
Tolerance is a distinguishing feature of Western culture: There is a widespread attitude that people should be allowed to say what they want even if one dislikes the message. Still, the degree of tolerance varies between and within countries, as well as over time, and if one values this kind of attitude, it becomes important to identify its determinants. In this study, we investigate whether the character of economic policy plays a role, by looking at the effect of changes in economic freedom (i.e., lower government expenditures, lower and more general taxes and more modest regulation) on tolerance in one of the most market-oriented countries, the United States. In comparing U.S. states, we find that an increase in the willingness to let atheists, homosexuals and communists speak, keep books in libraries and teach college students is, overall, positively related to preceding increases in economic freedom, more specifically in the form of more general taxes. We suggest, as one explanation, that a progressive tax system, which treats people differently, gives rise to feelings of tension and conflict. In contrast, the positive association for tolerance towards racists only applies to speech and books, not to teaching, which may indicate that when it comes to educating the young, (in)tolerant attitudes towards racists are more fixed.
Keywords: P10; P48; Z13; 330; Markets; Economic freedom; Tolerance; Taxation; Government; Generality; USA